2023
DOI: 10.1172/jci149834
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell activation in lungs during SARS-CoV-2 infection associated with lung pathology and severe COVID-19

Abstract: Lung inflammation is a hallmark of Coronavirus disease 2019 (COVID-19) in patients who are severely ill, and the pathophysiology of disease is thought to be immune mediated. Mast cells (MCs) are polyfunctional immune cells present in the airways, where they respond to certain viruses and allergens and often promote inflammation. We observed widespread degranulation of MCs during acute and unresolved airway inflammation in SARS-CoV-2-infected mice and nonhuman primates. Using a mouse model of MC deficiency, MC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Other than brain, the rapidly induced MC degranulation in various tissues, including lung, trachea, heart, and intestines, could offer an explanation of multi-focal SARS-CoV-2–induced inflammation and damages (our submitted data). Our research, along with others’, has recently reported that SARS-CoV-2–induced MC massive accumulation and rapid degranulation caused lung inflammation and injury in mice and nonhuman primates ( Wu et al., 2021 , 2022 ; Tan et al., 2023 ). The severity of SARS-CoV-2 infection is associated with high number of alveolar MCs and their degranulation ( Krysko et al., 2022 ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Other than brain, the rapidly induced MC degranulation in various tissues, including lung, trachea, heart, and intestines, could offer an explanation of multi-focal SARS-CoV-2–induced inflammation and damages (our submitted data). Our research, along with others’, has recently reported that SARS-CoV-2–induced MC massive accumulation and rapid degranulation caused lung inflammation and injury in mice and nonhuman primates ( Wu et al., 2021 , 2022 ; Tan et al., 2023 ). The severity of SARS-CoV-2 infection is associated with high number of alveolar MCs and their degranulation ( Krysko et al., 2022 ).…”
Section: Discussionsupporting
confidence: 72%
“…In SARS-CoV-2 infection, the post-mortem lung biopsies of COVID-19 patients show a massive increase in the density of perivascular and septal MCs ( Motta Junior et al., 2020 ; Budnevsky et al., 2022 ; Schaller et al., 2022 ). Our research, along with others’, has recently reported that SARS-CoV-2–induced massive MC accumulation and rapid degranulation caused lung inflammation and damage both in mice and nonhuman primate models ( Wu et al., 2021 , 2022 ; Tan et al., 2023 ). The severity of SARS-CoV-2 infection is associated with high number of alveolar MCs and their degranulation ( Krysko et al., 2022 ).…”
Section: Introductionsupporting
confidence: 73%
“…In addition to such allergic reactions, we suggest that the co-sensing of ATP and IL-33 by MCs also contributes to the development of pulmonary diseases such as COVID-19. Interestingly, in lung tissues of SARS-CoV2-infected humans and mice, hyperactivated MCs were found [19][20][21]. Thereby, the presence of hyperactivated MCs correlated with the strongly elevated levels of IL-33 [22,23], ATP [24] and MC proteases [19] in the serum of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 89%
“…In this context, degranulating mast cells, as well as elastase and NET-secreting neutrophils, are potential candidates for KKS amplification during SARS-CoV-2 infection ( Figure 3 , panel 1). Mast cell degranulation was detected in the lungs of mouse and nonhuman primate models of COVID-19 [ 158 ]. Also, increased levels of circulating chymase were detected in hospitalized patients in comparison with healthy donors or individuals with mild disease.…”
Section: Kks Activation and Bradykinin Signaling In Respiratory Viral...mentioning
confidence: 99%